Optical Properties of Solids: An Introductory Textbook / Kitsakorn Locharoenrat (Author) - Locharoenrat, Kitsakorn (Pan Stanford publishing, 2016)
This textbook presents the general point of views of the optical properties of solids and gives an overview of the landscape of optics in solid-state materials, especially focusing on optical imaging techniques. It presents the background of electromagnetic theory, which is based on Maxwell’s equations. It shows how to manipulate Maxwell’s equations in differential forms by utilizing vector analysis and how to calculate the electric field emerging from a single charge and from charge distributions in conductors and dielectrics under Maxwell’s boundary conditions. It analyzes the optical spectra from localized electronic states and goes over some well-known phenomena currently under research, such as nonlinear optical response of materials. It also gives a background on optical microscopy, focusing on the optical response of modern confocal microscopy on asymmetric materials, and introduces optical tomographic techniques to identify the locations and profiles of matter, concentrating on fluorescence diffuse optical tomography used as a probe in deep biological tissue.